(untitled) (Research, Society and Development, 2024)
Physical exercise practice can contribute significantly to functionality improvement, self-efficacy, the recovery process, independence, and socialization of people, in addition to being an essential resource in the fight against sedentary lifestyles and associated comorbidities. In this context, the present study aimed to conduct a bibliographic survey on the impact of physical exercise on the functionality of individuals with Spinal Cord Injury (SCI). This is an integrative literature review, conducted based on the PRISMA criteria. The Cochrane, PubMed, Scielo, and Pedro databases were consulted using the descriptors: Physical Exercise, Spinal Cord, Spine, and Functional Physical Performance in Portuguese and their respective translations into English. Initially, 351 articles were identified, of which 8 met the inclusion criteria and were reviewed. The sample examined included 756 participants, with complete and incomplete lesions, quadriplegic and paraplegic. The results show that maintaining an active routine promotes increased self-efficacy in exercise, greater social participation, engagement, and satisfaction, as well as improvements in physical and functional performance. We conclude that physical exercise not only contributes to a more robust health status and the prevention of chronic diseases, but also plays a key role in improving physical, mental, and social functions, resulting in better quality of life and greater personal satisfaction for individuals with SCI.